Pembelajaran Orang Dewasa: Tutorial Webinar (Tuweb) melalui Microsoft Teams Mahasiswa PGSD Universitas Terbuka di Era Pandemi - Alpin Herman Saputra; Hartati Hartati; Steven Anthony (Universitas Sebelas Maret, 2021)
Primary Education of Universitas Terbuka students are students of Elementary School Teacher Education (PGSD) and Early Childhood Education (PGPAUD) study programs who have been teachers in schools for at least 1 (one) year of teaching. PGSD students in normal circumstances carry out direct learning through Face-to-Face Tutorials (TTM) but in the pandemic era, they adapt to the Webinar Tutorial (Tuweb) using the Microsoft team. Tuweb is synchronous learning. Adult learning styles (andragogy) in the aspect of self-concept (emotionally stable students, they are adults whose age, cognitive, and development are mature), the concept of experience (the requirement to become a student in the teaching field of at least one year of teaching, is proven with a Decree (SK) from the relevant agency, the concept of learning readiness, time perspective or learning orientation. The average score of the andragogy ability of the students is 84.8 or in the high category